2020
DOI: 10.1177/0194599820951473
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Nodal Metastases and Predictors of Occult Disease in HPV‐Associated Oropharynx Cancer

Abstract: Objective For human papilloma virus–associated oropharynx squamous cell carcinoma (HPV+ OPSCC), we evaluated the distribution of neck-level lymph node (LN) metastasis, based on postsurgical histopathology, and the incidence of and risk factors for occult LN metastases, as these patterns need clarification for this newer cancer subset. Study Design Retrospective cohort study. Setting National Cancer Database (NCDB). Methods We analyzed 2358 patients in the NCDB with HPV+ OPSCC who underwent neck dissection (ND)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…Recently, focus has been on HPV-positive OPSCC due to its increasing incidence in Western countries; the majority of cases in the United States are potentially HPV positive, particularly among recent birth cohorts, perhaps resulting from changes in sexual behaviors. (9)(10)(11)(12). The majority of OPSCCs in some regions, such as China, are still HPV negative (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, focus has been on HPV-positive OPSCC due to its increasing incidence in Western countries; the majority of cases in the United States are potentially HPV positive, particularly among recent birth cohorts, perhaps resulting from changes in sexual behaviors. (9)(10)(11)(12). The majority of OPSCCs in some regions, such as China, are still HPV negative (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…For patients who undergo END, only 4.0% (17/423) have occult lymph node metastasis at level IV. Hence, the authors considered that therapeutic neck dissection should encompass at least level II, III, and IV and that END encompassing level II-III is su cient for adequate pathologic staging and treatment of HPV-positive OPSCC(10) Nonetheless, research on level IV neck dissection in cN0 OPSCC remains controversial. Evidence to date largely relates to the distribution of cervical lymph node metastasis based on observational studies.…”
mentioning
confidence: 99%
“…Current guidance recommends concurrent ipsilateral neck dissection of levels II–IV in all patients undergoing lateralized primary tumor surgical resection for OPSCC, regardless of HPV status 7 . Selective neck dissection (ND) in levels II–IV has been found to provide excellent disease control with low morbidity 8,9 . Cervical nodal levels I and V have demonstrated low (<10%) rates of positive cervical lymph nodes in this population 9 and thus are routinely excluded 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Selective neck dissection (ND) in levels II–IV has been found to provide excellent disease control with low morbidity 8,9 . Cervical nodal levels I and V have demonstrated low (<10%) rates of positive cervical lymph nodes in this population 9 and thus are routinely excluded 10 . Recent studies have suggested that excision of levels II and III alone may be sufficient treatment in this patient population, particularly for those patients without clinical evidence of nodal disease 9,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation